Adsorption Characteristics of Activated Carbon for the Reclamation of Eosin Y and Indigo Carmine Colored Effluents and New Isotherm Model - Ratna Surya Alwi; Ramakrishnan Gopinathan; Avijit Bhowal; Chandrasekhar Garlapati (Molecules, 2020)
The adsorption response of eosin Y and indigo carmine acid dyes on activated carbon as a function of system temperature for a fixed concentration was investigated at various temperatures via adsorption isotherms and their thermodynamic quantities such as enthalpy, entropy, and Gibbs free energy changes. The adsorption data were exploited to develop a new adsorption isotherm. The new isotherm was developed with the spirit of solid–liquid phase equilibrium and regular solution theory. The proposed model has four adjustable constants and correlates adsorption isotherm in terms of the system temperature and melting temperature of the dye. The effect of pH on the removal of acid dyes was reported. The pH variation was observed to affect the adsorption efficiency. The removal of eosin Y and indigo carmine decreased from 99.4% to 82.6% and 92.38% to 79.48%, respectively, when the pH of the solution varied from 2 to 12. The thermodynamic analysis of the process reveals that the process of the removal of acid dyes is exothermic and spontaneous. Moreover, the kinetics parameters of the batch process are reported.